Effect of biological factors on latency of pattern-reversal visual evoked potentials associated with cathode ray tubes and liquid crystal display monitors in normal young subjects - Ura, Midori; Matsuo, Mutsuki; Yamazaki, Haruna; Morita, Hiroshi (Documenta ophthalmologica, 2021)
Purpose Owing to several factors, peak latencies of pattern-reversal visual evoked potentials (p-VEP) are delayed when viewing liquid crystal display (LCD) monitors compared to those evoked when viewing cathode ray tube (CRT) monitors. However, few studies have examined whether biological factors affect latency in LCD. This study aimed to investigate whether biological factors caused latency changes in LCD among young subjects. Methods Twenty-eight subjects (56 eyes) aged 21–29 years (mean ± SD, 22.7 ± 1.7) participated in this study. We recorded output from each eye twice for both CRT and LCD monitors under the same conditions for monocular p-VEP. The peak latencies of three components (N75, P100, and N145) were compared between these two monitors. Results All peak latencies recorded with LCD were delayed compared to those recorded with CRT: N75, 9.7 ± 2.5 ms; P100, 10.1 ± 3.0 ms; and N145, 8.4 ± 6.2 ms (all p < 0.001). The degree of latency delay varied depending on the components. Moreover, all peak latencies of CRT appeared earlier than standard values of N75, P100, and N145. Conclusions These findings suggest that the following aspects should be considered when assessing biological factors that may affect latency: components might influence latency changes; a young age could be related to an early appearance of peak latencies; inter-individual differences might cause latency change. These biological factors should be considered as possible causes for the varying latencies in an LCD monitor. Further studies should include healthy adults with a wider age range to assess the effects of age on latency.